2014
DOI: 10.1016/j.gaitpost.2013.07.122
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of sensor-based sit-to-stand peak power to the effects of training leg strength, leg power and balance in older adults

Abstract: Increasing leg strength, leg power and overall balance can improve mobility and reduce fall risk. Sensor-based assessment of peak power during the sit-to-stand (STS) transfer may be useful for detecting changes in mobility and fall risk. Therefore, this study investigated whether sensor-based STS peak power and related measures are sensitive to the effects of increasing leg strength, leg power and overall balance in older adults. A further aim was to compare sensitivity between sensor-based STS measures and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 24 publications
2
53
0
2
Order By: Relevance
“…A decrease in rate of force development has been reported to be an important contributor to declining muscle function in older men (Thompson, Ryan, Sobolewski, Conchola, & Cramer, 2013) and a risk factor for falls in older women (Crozara et al, 2013). Although few previous studies have examined accelerometerderived measures of jerk, in one recent study maximum jerk was found to show expected improvements in response to training during a sit-to-stand activity in older people (Regterschot et al, 2014). Since rate of force development appears to be related to the ability to execute movements such as sit to stand, we reasoned that maximum jerk as measured during the aerobics class may be related to chair rise time.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in rate of force development has been reported to be an important contributor to declining muscle function in older men (Thompson, Ryan, Sobolewski, Conchola, & Cramer, 2013) and a risk factor for falls in older women (Crozara et al, 2013). Although few previous studies have examined accelerometerderived measures of jerk, in one recent study maximum jerk was found to show expected improvements in response to training during a sit-to-stand activity in older people (Regterschot et al, 2014). Since rate of force development appears to be related to the ability to execute movements such as sit to stand, we reasoned that maximum jerk as measured during the aerobics class may be related to chair rise time.…”
Section: Discussionmentioning
confidence: 99%
“…By measuring elbow and knee torque, Frontera et al (1991) reported that muscle strength in elders is 27% lower than the adults [15]. Decrease in muscle strength, on the other hand, induced loss of postural balance and control [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Slight changes in physical function are difficult to measure in a timed performance 25) . Conversely, a sensor-based test can accurately measure changes in physical function 26) . For these reasons, a sensor-based test may be a more sensitive evaluation method and have a stronger predictive capability than the five-times STS test.…”
Section: Strengths and Limitationsmentioning
confidence: 99%